2018
DOI: 10.1038/s41590-018-0052-z
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 9 antagonizes antibody affinity maturation

Abstract: Key events in T cell-dependent antibody responses, including affinity maturation, are dependent on the B cell’s presentation of antigen to helper T cells at critical check points in germinal center formation in secondary lymphoid organs. Here we show that Toll-like receptor 9 (TLR9) signaling blocked the ability of antigen-specific B cells to capture, process and present antigen and to activate antigen-specific helper T cells in vitro. In a mouse model in vivo and in a human clinical trial the TLR9 agonist, Cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…TLR7 and TLR9 are both expressed by murine and human B cells [346]. The CpG ODN mediated activation of TLR9 on B cells increased the magnitude of the antibody response to the protein antigen but inhibited process of antibody affinity maturation both in mice and in human clinical trials [347]. Thus, the activation of TLR9 on B cells has a potential to affect antibody response during various vaccination strategies where various TLR9-agonists are used as adjuvants.…”
Section: B Cells and Pattern Of Tlr Expressionmentioning
confidence: 99%
“…TLR7 and TLR9 are both expressed by murine and human B cells [346]. The CpG ODN mediated activation of TLR9 on B cells increased the magnitude of the antibody response to the protein antigen but inhibited process of antibody affinity maturation both in mice and in human clinical trials [347]. Thus, the activation of TLR9 on B cells has a potential to affect antibody response during various vaccination strategies where various TLR9-agonists are used as adjuvants.…”
Section: B Cells and Pattern Of Tlr Expressionmentioning
confidence: 99%
“…However, if naive B cells capture antigen from the FDC in the presence of TLR agonists, as would occur in malaria, the B cells would be unable to process and present the antigen to T H cells. 49 We demonstrated that signaling through TLR9 in response to its ligand CpG induced rapid naive B cell proliferation but blocked BCR-dependent antigen processing and presentation resulting in a failure of B cells to interact with and activate CD4 + T cells in vitro. Considering the first checkpoint in antigen-driven B cell activation in which naive B cells engage antigen and signal in response to it, it has been suggested that chronic exposure to parasite-derived low affinity "decoy" antigens might function to divert B cells to ineffective low affinity non-GC responses.…”
Section: Under S Tanding At Ypic Al Mbc E Xpan S I On In the Contementioning
confidence: 89%
“…46 Recent studies also suggest that parasite PAMPs, in particular ligands for TLR9, including hemozoin, 48 may dramatically alter the naive B cell's ability to pass through this first checkpoint. 49 We demonstrated that signaling through TLR9 in response to its ligand CpG induced rapid naive B cell proliferation but blocked BCR-dependent antigen processing and presentation resulting in a failure of B cells to interact with and activate CD4 + T cells in vitro. 49 BCR-dependent processing was blocked after antigen internalization during the transport of antigen to acidic intracellular antigen-processing compartments.…”
Section: Under S Tanding At Ypic Al Mbc E Xpan S I On In the Contementioning
confidence: 89%
See 2 more Smart Citations